Rancang Bangun Pompa Torak Dengan Sistem Penggerak Kincir Air Untuk Pengairan Lahan Pertanian - Hendra, Hendra; Sisworo, Raden Sisworo; Hasanudin, La (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
Indonesia has large water sources, but cannot be fully utilized, for example in the agricultural sector because of the difference in land height and water sources, in connection with that we need pumps that can be used to supply water to the land. The purpose of this research is to design, manufacture pumps, determine the materials used and their strengths, and determine the power generated. Research methods include the design and manufacture of pumps as well as material selection and strength calculations. The results showed that the material for the piston was galvanized pipe with a tensile stress of 330 N/mm2, 3mm thick, the piston rod was a bolt with a tensile stress of 60 N/mm2, the cylinder used PVC pipe with a tensile stress of 21.933 N/mm2, 4.5 mm thick. , the connecting rod and shaft are made of standard assental iron with a tensile stress of 568.7 N/mm2, the sprocket uses a standard spretpat motor with a tensile stress of 509.94 N/mm2, and the chain uses a motor chain, length 1035.5 mm, tensile stress 608.01 N/mm2 and the power generated is 46.96 watts.Kata kunci: alternative, design, pump, reciprocating pump